Trafficking of K63-polyubiquitin-modified membrane proteins in a macroautophagy-independent pathway is linked to ATG9A - Scavone, Francesco; Lian, Sharon; Eskelinen, Eeva-Liisa; Cohen, Robet E; Yao, Tingting (United States, 2025)
Cytoplasmic K63-linked polyubiquitin signals have well-established roles in endocytosis and selective autophagy. However, how these signals help to direct different cargos to different intracellular trafficking routes is unclear. Here we report that, when the K63-polyubiquitin signal is blocked by intracellular expression of a high-affinity sensor (named Vx3), many proteins originating from the plasma membrane are found trapped in clusters of small vesicles that colocalize with ATG9A, a transmembrane protein that plays an essential role in autophagy. Importantly, whereas ATG9A is required for cluster formation, other core autophagy machinery as well as selective autophagy cargo receptors are not required. Although the cargos are sequestered in the vesicular clusters in an ATG9-dependent manner, additional signals are needed to induce LC3 conjugation. Upon removal of the Vx3 block, K63-polyubiquitylated cargos are rapidly delivered to lysosomes. These observations suggest that ATG9A plays an unexpected role in the trafficking of K63-polyubiquitin-modified membrane proteins.